A new methodological support for control and optimization of manufacturing systems in the context of product customization. (4th July 2021) - Jaegler, Yann; Jaegler, Anicia; Mhada, Fatima Zahra; Trentesaux, Damien; Burlat, Patrick
ABSTRACT: Manufacturers more and more need to customize their products to respond to customer demand and differentiate from competitors. The present paper deals with key questions related to the implementation of production control systems in a high product mix and/or high routing mix environment generated by product customization. ConWip (CONstant Work In Progress) provides a sustainable, effective and adaptive production control system. The objective of the paper is to help manufacturers to optimize their production control system in product customization manufacturing environments. Four models that generate different generic routings are presented and tested with a sample of data from an industrial case. These routings are implemented into Wipsim, an engineering tool, which allows the optimized parameters for each routing to be calculated. Our experiments show that our models generated worthwhile generic routings and help manufacturers choose among them, depending on their own products customization specific context.